My mind, your mind, and God's mind: How children and adults conceive of different agents' moral beliefs. (16th January 2018) - Heiphetz, Larisa; Lane, Jonathan D.; Waytz, Adam; Young, Liane L.
Abstract : Extending prior research on belief attributions, we investigated the extent to which 5‐ to 8‐year‐olds and adults distinguish their beliefs and other humans' beliefs from God's beliefs. In Study 1, children reported that all agents held the same beliefs, whereas adults drew greater distinctions among agents. For example, adults reported that God was less likely than humans to view behaviors as morally acceptable. Study 2 additionally investigated attributions of beliefs about controversial behaviours (e.g., telling prosocial lies) and belief stability. These data replicated the main results from Study 1 and additionally revealed that adults (but not children) reported that God was less likely than any other agent to think that controversial behaviours were morally acceptable. Furthermore, across ages, participants reported that another person's beliefs were more likely to change than either God's beliefs or their own beliefs. We discuss implications for theories regarding belief attributions and for religious and moral cognition. Statement of contribution What is already known on this subject Preschoolers can attribute different beliefs to different humans Children and adults attribute greater cognitive capacities to God than to humans What the present study adds Children attribute the same moral beliefs to God and humans Adults distinguish among different agents' minds when attributing moral beliefs Developmental differences are less pronounced in judgements of belief stability